Bipedicled Nipple-Sparing Mastectomy Versus Traditional Nipple-Sparing Mastectomy: Comparison of 2 Alternative Techniques in Order to Save Nipple-Areola Complex. Issue 4 (April 2020) - Falco, Giuseppe; Curcio, Annalisa; Marongiu, Francesco; Buggi, Federico; Mingozzi, Matteo; Mele, Simone; Ferrari, Guglielmo; Folli, Secondo
Abstract : Background: Nipple-areola complex–sparing mastectomy (NSM) represents, when a mastectomy is unavoidable, the best treatment possible that can be offered to attenuate the negative impact of surgery on patients' quality of life. Unfortunately, NSM can be used only in selected patients with small and nonptotic breasts. In order to save the nipple-areola complex (NAC) also in patients with large and ptotic breast, otherwise subjected to a skin-sparing mastectomy with the sacrifice of the NAC, we described the bipedicled nipple-sparing mastectomy (BNSM). The aim of this study is to obtain a formal outcome assessment of BNSM and analyze the complications rate of this technique compared with traditional NSM. We furthermore attempt to describe the surgical procedures present in the literature that allow to preserve NAC also in large and ptotic breasts presenting the complication rates observed and comparing with our technique. Aesthetic outcome has also been evaluated. Methods: We retrospectively reviewed 42 procedures of consecutive patients undergoing immediate reconstruction with tissue expanders after NSM (20 patients) or BNSM (19 patients). We divided them in 2 groups focused on surgical complications and aesthetic outcome. Results: On a total of 42 procedures, the principal major complication was dehiscence of surgical wound procedures needing 1-day surgery revision occurring in 3 (14.3%) of the BNSM group and 1 (4.8%) of the NSM group, whereas as principal minor complication 4 partial NAC necrosis not requiring surgery in BNSM (19%) and 2 (9.5%) in NSM. No tissue expanders required explantation. Concerning cosmetic results, the overall appearance of the breast and NAC was acceptable in 85.7 % and 77.2%, respectively, in the NSM group and 80.7% and 66.7%, respectively, in the BNSM group. Conclusions: Bipedicled nipple-sparing mastectomy is a valid technique to improve patients' quality of life in large and ptotic breasts otherwise candidate to a skin-sparing mastectomy, but only a progressive learning curve can minimize complications. No significant statistical differences have been observed in terms of complication rates and aesthetical outcomes between the 2 groups. An accurate selection of patients is mandatory in order to obtain low complication rates and good aesthetical outcome.